HER2 induces cell proliferation and invasion of non-small-cell lung cancer by upregulating COX-2 expression via MEK/ERK signaling pathway - Chi, Feng (Dove Medical Press, 2016)
HER2 positivity has been well studied in various cancers, but its importance in non-small-cell lung cancer (NSCLC) is still being explored. In this study, quantitative reverse transcription polymerase chain reaction (qRT-PCR) was performed to detect HER2 and COX-2 expression in NSCLC tissues. Then, pcDNA3.1-HER2 was used to overexpress HER2, while HER2 siRNA and COX-2 siRNA were used to silence HER2 and COX-2 expression. MTT assay and invasion assay were used to detect the effects of HER2 on cell proliferation and invasion. Our study revealed that HER2 and COX-2 expression were upregulated in NSCLC tissues and HER2 exhibited a significant positive correlation with the levels of COX-2 expression. Overexpression of HER2 evidently elevated COX-2 expression, while silencing of HER2 evidently decreased COX-2 expression. Furthermore, overexpressed HER2 induced the ERK phosphorylation, and this was abolished by the treatment with U0126, a pharmacological inhibitor of MEK, an upstream kinase of ERK. HER2-induced expression and promoter activity of COX-2 were also suppressed by U0126, suggesting that the MEK/ERK signaling pathway regulates COX-2 expression. In addition, HER2 induced activation of AKT signaling pathway, which was reversed by pretreatment with U0126 and COX-2 siRNA. MTT and invasion assays revealed that HER2 induced cell proliferation and invasion that were reversed by pretreatment with U0126 and COX-2 siRNA. In this study, our results demonstrated for the first time that HER2 elevated COX-2 expression through the activation of MEK/ERK pathway, which subsequently induced cell proliferation and invasion via AKT pathway in NSCLC tissues.